Tackling the wanderer: the mouse parathyroids - Munjal, Manish; Kaur, Japneet; Singh, Amanjit; Kaur, Amanjot; Porshia, Rishi; Munjal, Shubham; Bains, Anmol (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Parathyroid surgery in aching, groaning, moaning, presentation has a successful outcome with intraoperative PTH descalating to less than 50% of the preoperative value. The inferior parathyroids are commonly not at the expected location with respect to the thyroids. Surgical pointers and wide exposure are the key to quick access with minimal collateral tissue trauma.